FACTORS INFLUENCING STUDENTSâ SELECTION OF UNIVERSITIES: THE CASE OF OMAN - Echchabi, Abdelghani; Al-Hajri, Salim (Journal of Education Reseach and Evaluation, 2018)
The main purpose of the study was to examine the factors that mostly influence studentsâ selection of the universities where they enrolled, in the Omani context. The study used mean values to rank the factors based on the studentsâ responses. The study covered a sample of 384 respondents from various Omani regions and used the mean value to examine the factors that influence studentsâ selection of their respective universities. The findings revealed that the main factor for university selection is the university reputation, followed by completion time, academic quality, as well as the academic staff qualifications. These findings have significant contributions to the Omani universities, as well universities in similar contexts. Particularly, it provides the universities with insights on the main dimensions and characteristics to emphasize in order to enhance their overall performance.